Black soldier fly larvae effectively degrade lincomycin from pharmaceutical industry wastes. (1st April 2022) - Luo, Xingyu; Yang, Qian; Lin, Yueting; Tang, Zhijun; Tomberlin, Jeffery K.; Liu, Wen; Huang, Yongping
Abstract: Lincomycin fermentation residues (LFR) are the byproducts from the pharmaceutical industry, and contain high concentrations of antibiotics that could pose a threat to the environment. Here, we report that black soldier fly larvae (BSFL) and associated microbiota can effectively degrade LFR and accelerate the degradation of lincomycin in LFR. The degradation rate of lincomycin in LFR can reach 84.9% after 12 days of BSFL-mediated bioconversion, which is 3-fold greater than that accomplished with natural composting. The rapid degradation was partially carried out by the BSFL-associated microbiota, contributing 22.0% of the degradation in the final composts. Based on microbiome analysis, we found that the structure of microbiota from both BSFL guts and BSFL composts changed significantly during the bioconversion, and that several bacterial genera were correlated with lincomycin degradation. The roles of the associated microbiota in the degradation were further verified by the ability of two larval intestinal bacterial isolates and one bacterial isolate from BSFL composts to lincomycin degradation. The synergy between BSFL and the isolated strains resulted in a 2-fold increase in degradation compared to that achieved by microbial degradation alone. Furthermore, we determined that the degradation was correlated with the induction of several antibiotic resistant genes (ARGs) associated with lincomycin degradation in larval guts and BSFL composts. Moreover, the environmental conditions in the BSFL composts were found to be conducive to the degradation. In conclusion, these findings demonstrate that the BSFL-mediated bioconversion of LFR could effectively reduce residual lincomycin and that the associated microbiota play crucial roles in the process. Highlights: Black soldier fly degrades lincomycin from pharmaceutical industry residues. Gut and compost microbiota contribute to lincomycin degradation. Lincomycin-degrading strains are isolated from larval guts and composts. Larvae and isolated strains have synergistic effects on antibiotic degradation. Environment in composts treated by the larvae is conducive to the degradation.